2018
DOI: 10.1177/1934578x1801300212
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Constituents of Dalbergia tonkinensis and Structural-Bioactive Highlights

Abstract: The vulnerable plant Dalbergia tonkinensis Prain, is a rare species, native to Vietnam. Phytochemical investigations and biological evaluations of this species are quite limited. Antimicrobial screening has suggested that, at the low dose of 1.0 mg/mL, the methanol extracts of the leaf, stem bark, and root, as well as chloroform fraction of heartwood can serve as useful sources against seven gram-positive skin microbacteria, Bacillus cereus (ATCC27522), Escherichia coli (JM109), Staphylococcus aureus (ATCC2592… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The structural differences, molecular size, stereochemistry, length of atomic bonds, and extra-or intramolecular hydrogen bonds, especially in terms of the behavior of hydroxyl groups, can be seen as basic characteristics to prove the pharmacological effects of a studied molecule. 3 As a consequence, a comprehensive analysis of structural and electronic descriptors of 2-phenylbenzofuran derivatives 1-16 is always recognized as the best way to forecast the radical scavenging capacity, along with the three antioxidant mechanisms. In the current paper, we provide computational outcomes for all studied compounds 1-16 at the DFT-B3LYP/6-311++G(d,p) level.…”
Section: Geometrical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The structural differences, molecular size, stereochemistry, length of atomic bonds, and extra-or intramolecular hydrogen bonds, especially in terms of the behavior of hydroxyl groups, can be seen as basic characteristics to prove the pharmacological effects of a studied molecule. 3 As a consequence, a comprehensive analysis of structural and electronic descriptors of 2-phenylbenzofuran derivatives 1-16 is always recognized as the best way to forecast the radical scavenging capacity, along with the three antioxidant mechanisms. In the current paper, we provide computational outcomes for all studied compounds 1-16 at the DFT-B3LYP/6-311++G(d,p) level.…”
Section: Geometrical Analysismentioning
confidence: 99%
“…2 Natural products, especially compounds isolated from plants, have historically proven their positive values in terms of therapeutic potency, whereas the employment of synthetic compounds is accompanied by high costs, a long duration of treatment, adverse effects and limitations in drug efficacy. 3 Thus, scientic approaches seeking new drug lead compounds are always expected.…”
Section: Introductionmentioning
confidence: 99%
“…The global health problem in developing countries is becoming increasingly involved in growing and expanding of microbacteria. Historical records have accumulated evidence showing that the use of traditional antibiotics, which are derived from synthetic substances, is always accompanied by a long duration of treatment, high cost, and drug resistance [48]. Therefore, calls for new antibiotic drugs from natural sources in the fight against multidrug-resistant bacteria are always strategy.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…A phytochemical study on this species has led to the identification of different types of compounds [17], including flavonoids, isoflavonoids, and neoflavonoids, endowed with various, interesting, pharmacological activities [18][19][20][21][22][23][24]. Curiously, the term "neoflavonoids" was first proposed by Ollis in 1966 when he found that various dalbergiones and dalbergiquinols are characteristic of the Dalbergia species [25].…”
Section: Introductionmentioning
confidence: 99%